2019
DOI: 10.1016/j.apor.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of nylon mooring lines for a floating wind turbine

Abstract: As current attention of the offshore industry is drawn by developing pilot farms of Floating Wind Turbines (FWTs) in shallow-water between 50m and 100m, the application of nylon as a mooring component can provide a more cost-effective design. Indeed, nylon is a preferred candidate over polyester for FWT mooring mainly because of its lower stiffness and a corresponding capacity of reducing maximum tensions in the mooring system. However, the nonlinear behaviors of nylon ropes (e.g. load-elongation properties, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Also, smaller dimensions of mesh elements increase accuracy and also computations, which becomes more important for calculating the force applied to the structure. 23 Independence of numerical solution from mesh. Figure 7 shows an overview of the meshed structure in the software.…”
Section: Mesh Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, smaller dimensions of mesh elements increase accuracy and also computations, which becomes more important for calculating the force applied to the structure. 23 Independence of numerical solution from mesh. Figure 7 shows an overview of the meshed structure in the software.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Mooring system analysis was done for both ultimate limit state (ULS) and fatigue limit state (FLS) in the time domain. 23 The effects of the mooring configurations on the dynamic response of a submerged floating offshore wind turbine (SFOWT) were investigated in the work of Li et al In their study, the dynamic response of the platform, the tension in the mooring lines, and the bending moment in tower base and blade root were examined for a coupled dynamic system under four different mooring configurations. The results showed that the optimized mooring system presents a larger restoring force so that the structure has small movement in the harsh state of the sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of using nylon ropes for long-term mooring lines is relatively new as there is little available knowledge on the durability behaviour of such structures. Indeed, as Pham et al (2019) conclude in a very recent study "a comprehensive study on the critical fatigue damage mechanisms of nylon should be the topic of future work." It is therefore essential to generate further data on polyamide mooring ropes, in order to validate their use for this application.…”
Section: Introductionmentioning
confidence: 99%
“…The requirements for floating offshore wind are closer to those of the oil and gas industry, but the platforms are smaller and are subjected to larger movements. In this case, more mooring line compliance is needed to avoid generating high cyclic loads and materials such as polyester may be too stiff; therefore, there has been considerable recent interest in polyamide ropes for this application [7][8][9].…”
Section: Introductionmentioning
confidence: 99%